Arabic Language Test in the Perspective of Competency-Based Curriculum for Students of Madrasah Aliyah Negeri 3 Malang - Qodri, Muhammad (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
The purpose of this research is to describe the items of the final Arabic language test questions for students of the Government Islamic Secondary School 3 Malang in the light of the proficiency based curriculum (KBK). This research is the type of desk research on the descriptive analytical approach qualitative approach. The data sources in this research are in the form of Arabic language question documents for the final school exam in the curriculum based on proficiency. The data were collected in the manner of documents and interviews. The results of this research are in harmony between the items of the final Arabic language test questions for students of the Madrasah Aliyah 3 Malang in the academic year 2011/2012 with the curriculum on the basis of competence, which contains: Reading skill questions are also suited to normative and basic competence, although these items do not contain items of phonics questions in language questions and listening, speaking and writing items in language skills questions.